2022
DOI: 10.2147/dmso.s366100
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Body Mass Index with Clinicopathologic Parameters in Patients with Idiopathic Membranous Nephropathy

Abstract: To investigate the association between body mass index (BMI) and clinicopathologic parameters in patients with idiopathic membranous nephropathy (IMN). Methods: This study was retrospective and included patients with biopsy-proven IMN from 2018 to 2021 in Hebei General Hospital. Patients were categorized into two groups based on BMI. Clinical and histopathologic data were analyzed at the time of renal biopsy. Pathological data included immunofluorescence staining, glomerulosclerosis (GS, 0-2), mesangial cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…[41][42][43] Previous studies demonstrate that the change in BMI is an important predictor of proteinuria, which is associated with decreased podocyte density and number and mesangial cell proliferation. 4,44,45 SGLT-2 inhibitors, GLP-1 receptor agonist and dual glucose-dependent insulinotropic polypeptide-GLP-1 receptor agonist are new antidiabetic drugs that have been associated with a reduction in weight, proteinuria and/or progression of renal disease. [46][47][48][49] The kidney protection of these new antidiabetic drugs has been considered to be a consequence of inhibition of inflammation, restored insulin sensitivity and decreasing the level of autophagy in ORG model mice.…”
Section: Dovepressmentioning
confidence: 99%
“…[41][42][43] Previous studies demonstrate that the change in BMI is an important predictor of proteinuria, which is associated with decreased podocyte density and number and mesangial cell proliferation. 4,44,45 SGLT-2 inhibitors, GLP-1 receptor agonist and dual glucose-dependent insulinotropic polypeptide-GLP-1 receptor agonist are new antidiabetic drugs that have been associated with a reduction in weight, proteinuria and/or progression of renal disease. [46][47][48][49] The kidney protection of these new antidiabetic drugs has been considered to be a consequence of inhibition of inflammation, restored insulin sensitivity and decreasing the level of autophagy in ORG model mice.…”
Section: Dovepressmentioning
confidence: 99%
“…Studies on the relationship between obesity and MN are scarce. Only one study 32 demonstrated that obesity may play an essential role in mesangial lesions of PMN. Obesity has currently become an epidemic.…”
Section: Discussionmentioning
confidence: 99%
“…We found individuals with ratios ≤4.25 were predominantly female, without hypertension, and had lower BMIs, DBPs, UAs and UPROs compared to those with higher ratios (Supplementary Table S1). Although these features strongly associate with TA risk (5,33,(36)(37)(38), their collective impact enhances among those with ratios >4.25, reducing the TG/HDL-C ratio's effect. In contrast, with fewer impactful risk factors present below 4.25, the ratio's influence is amplified-likely contributing to the nonlinear relationship.…”
Section: Figurementioning
confidence: 99%